Magnesium aluminate spinel brick produced from alumina-chromium slag and preparation method of magnesium aluminate spinel brick
By using aluminum-chromium slag as raw materials, magnesium-aluminum spinel bricks were prepared, which solved the problems of high production costs and tight supply of raw materials in the prior art, and achieved the effects of cost reduction, performance improvement and widespread application.
Patent Information
- Application Number
- CN202411872013.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-14
AI Technical Summary
The production cost of existing magnesium-aluminum spinel bricks is high and the supply of raw materials is tight, which makes it difficult to alleviate the problem of depletion of refractory raw materials resources.
Magnesium aluminum spinel bricks are prepared through specific ratios and process flows (including preparation, mixing, forming and drying).
It reduces production costs, improves slag corrosion resistance and thermal shock performance, has high cost performance, and is suitable for working lining bricks in molten pool parts of various specifications and models, and is widely used.
Smart Images

Figure CN119430966A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, and in particular to a magnesia-alumina spinel brick produced from aluminum-chromium slag and a preparation method thereof. Background Art
[0002] Magnesium-aluminum spinel bricks have a longer service life than traditional carbon-containing materials (magnesium-aluminum carbon bricks, aluminum-magnesium carbon bricks) when used as the working layer of the molten pool of the refined steel ladle. They have better resistance to slag erosion, are carbon-free, have a slow melting loss rate, and produce fewer inclusions in the molten steel during use. They are the preferred material for smelting low-carbon steel and ultra-low-carbon steel. Magnesium-aluminum spinel bricks are made of high-quality white corundum, but the current supply of high-quality white corundum raw materials is tight and the price is gradually rising, resulting in high production costs and unable to alleviate the problem of tight supply. Therefore, it is necessary to develop a substitute with comparable performance, low cost and unrestricted source to alleviate the current situation of depletion of refractory raw material resources. Summary of the invention
[0003] The first purpose of the present invention is to provide a magnesia-alumina spinel brick produced by aluminum-chromium slag to address the deficiencies of the prior art; the second purpose is to provide a method for preparing magnesia-alumina spinel brick produced by aluminum-chromium slag.
[0004] The first object of the present invention is achieved by the following technical scheme: comprising the following raw materials in mass percentage: 48-72% aggregate, 8-12% calcined α-Al2O3 powder CL370, 8-12% fused spinel powder AMS-78, 8-12% plate-like corundum powder, 2-4% fused magnesium powder, 0.5-1% silicon powder, 3-5% binder, and 2-2.2% water.
[0005] The second object of the present invention is achieved by the following technical solutions: S1. Prepare the materials, mix various raw materials according to the proportion and set aside; S2, mixing materials, first add water to the aggregate (reduced aluminum chromium slag coarse powder, reduced aluminum chromium slag medium powder, reduced aluminum chromium slag fine powder) and stir until wet, then add magnesium aluminum complex gel binder and stir for 5-7 minutes to make the binder completely melt and adhere to the aggregate, then add calcined α-Al2O3 micro powder CL370, fused spinel powder AMS-78, plate-like corundum powder, fused magnesium powder, and silicon micro powder and stir thoroughly for 25-30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
[0006] Beneficial effects of the present invention: The magnesium-aluminum spinel brick of the present invention has a higher volume density and a lower porosity. The original aluminum-chromium slag is used instead of plate-shaped corundum to improve the slag erosion resistance and thermal shock resistance of the product. The recycled chromium corundum is used as the main raw material to greatly reduce the cost and improve the use performance of the product. It has a high cost-effectiveness, is energy-saving and environmentally friendly, and can also be used to press working lining bricks of various specifications and models in the molten pool, and has a wide range of applications. On the other hand, aluminum-chromium slag is a by-product produced during the smelting of metallic chromium. Using it as a production material for magnesium-aluminum spinel bricks effectively solves the problems of its inconvenient handling and easy environmental damage, reduces the cost of harmless treatment, and greatly improves its utilization efficiency and added value. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is the SEM photo of the crucible after the static slag resistance test; Figure 2 This is a structural photograph of the crucible cross section after slag etching at 1450℃ for 3h. DETAILED DESCRIPTION
[0008] The present invention will be further described below with reference to the embodiments, but is not limited to the contents of the specification.
[0009] Example 1
[0010] A method for preparing magnesia-alumina spinel bricks produced by aluminum-chromium slag, specifically comprising the following steps: S1. Prepare materials, mix various raw materials in proportion, including the following raw materials in mass percentage: 48~72% aggregate, 8~12% calcined α-Al2O3 powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-shaped corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon powder, 3~5% binder, 2~2.2% water; wherein, The aggregate includes the following raw materials in percentage by mass: 8-12% coarse powder of reduced aluminum-chromium slag with a particle size of 3-5 mm; 25-35% medium powder of reduced aluminum-chromium slag with a particle size of 1-3 mm; 15-25% fine powder of reduced aluminum-chromium slag with a particle size of 0-1 mm; and the coarse powder, medium powder and fine powder of reduced aluminum-chromium slag are all recycled granular materials produced by high-temperature heat treatment of aluminum-chromium slag by carbon thermal reduction method. High-temperature heat treatment of aluminum-chromium slag by carbon thermal reduction method can obtain two products. Due to their different densities, they are separated by layers during the cooling process. The Al2O3 content (i.e. original aluminum-chromium slag) in most of the reduced products in the upper layer is as high as 90% (w) or more; The particle size of calcined α-Al2O3 powder is ≤0.044mm, the particle size of fused spinel powder AMS-78, plate-shaped corundum powder, and silica powder are 300~350 mesh respectively, and the particle size of fused magnesium powder is 150~200 mesh; The binder is a magnesium-aluminum complex gel binder chemically combined with inorganic water, and the magnesium-aluminum complex gel binder is 300-350 mesh; S2, mixing materials, first add 2~2.2% water to 48~72% aggregate (8~12% reduced aluminum chromium slag coarse powder, 25~35% reduced aluminum chromium slag medium powder, 15~25% reduced aluminum chromium slag fine powder) and stir until wet, then add 3~5% magnesium aluminum complex gel binder and stir for 5~7 minutes to make the binder completely melt and adhere to the aggregate, then add 8~12% calcined α-Al2O3 micro powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-like corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon micro powder and stir thoroughly for 25~30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; The technical indicators of the brick blank require a volume density of 3.0~3.05g / cm 3 , apparent porosity ≤12%, compressive strength at room temperature MPa≥60, flexural strength at room temperature MPa≥4; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
[0011] Example 2
[0012] S1. Prepare materials, mix various raw materials in proportion, including the following raw materials in mass percentage: 48~72% aggregate, 8~12% calcined α-Al2O3 powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-shaped corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon powder, 3~5% binder, 2~2.2% water; wherein, The aggregate includes the following raw materials in percentage by mass: 8-12% of coarse powder of reduced aluminum-chromium slag with a particle size of 3-5 mm; 25-35% of medium powder of reduced aluminum-chromium slag with a particle size of 1-3 mm; 15-25% of fine powder of reduced aluminum-chromium slag with a particle size of 0-1 mm; and the coarse powder, medium powder and fine powder of reduced aluminum-chromium slag are all recycled granular materials produced by subjecting aluminum-chromium slag to high-temperature heat treatment using a carbon thermal reduction method; The particle size of calcined α-Al2O3 powder is ≤0.044mm, the particle size of fused spinel powder AMS-78, plate-shaped corundum powder, and silica powder are 300~350 mesh respectively, and the particle size of fused magnesium powder is 150~200 mesh; The binder is a magnesium-aluminum complex gel binder chemically combined with inorganic water, and the magnesium-aluminum complex gel binder is 300-350 mesh; S2, mixing materials, first add 2~2.2% water to 48~72% aggregate (8~12% reduced aluminum chromium slag coarse powder, 25~35% reduced aluminum chromium slag medium powder, 15~25% reduced aluminum chromium slag fine powder) and stir until wet, then add 3~5% magnesium aluminum complex gel binder and stir for 5~7 minutes to make the binder completely melt and adhere to the aggregate, then add 8~12% calcined α-Al2O3 micro powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-like corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon micro powder and stir thoroughly for 25~30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; The technical indicators of the brick blank require a volume density of 3.0~3.05g / cm 3 , apparent porosity ≤12%, compressive strength at room temperature MPa≥60, flexural strength at room temperature MPa≥4; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
[0013] Example 3
[0014] S1. Prepare materials, mix various raw materials in proportion, including the following raw materials in mass percentage: 48~72% aggregate, 8~12% calcined α-Al2O3 powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-shaped corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon powder, 3~5% binder, 2~2.2% water; wherein, The aggregate includes the following raw materials in percentage by mass: 8-12% of coarse powder of reduced aluminum-chromium slag with a particle size of 3-5 mm; 25-35% of medium powder of reduced aluminum-chromium slag with a particle size of 1-3 mm; 15-25% of fine powder of reduced aluminum-chromium slag with a particle size of 0-1 mm; and the coarse powder, medium powder and fine powder of reduced aluminum-chromium slag are all recycled granular materials produced by subjecting aluminum-chromium slag to high-temperature heat treatment using a carbon thermal reduction method; The particle size of calcined α-Al2O3 powder is ≤0.044mm, the particle size of fused spinel powder AMS-78, plate-shaped corundum powder, and silica powder are 300~350 mesh respectively, and the particle size of fused magnesium powder is 150~200 mesh; The binder is a magnesium-aluminum complex gel binder chemically combined with inorganic water, and the magnesium-aluminum complex gel binder is 300-350 mesh; S2, mixing materials, first add 2~2.2% water to 48~72% aggregate (8~12% reduced aluminum chromium slag coarse powder, 25~35% reduced aluminum chromium slag medium powder, 15~25% reduced aluminum chromium slag fine powder) and stir until wet, then add 3~5% magnesium aluminum complex gel binder and stir for 5~7 minutes to make the binder completely melt and adhere to the aggregate, then add 8~12% calcined α-Al2O3 micro powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-like corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon micro powder and stir thoroughly for 25~30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; The technical indicators of brick blanks require a volume density of 3.0~3.05g / cm 3 , apparent porosity ≤12%, compressive strength at room temperature MPa≥60, flexural strength at room temperature MPa≥4; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
[0015] Example 4
[0016] S1. Prepare the materials. Prepare various raw materials in proportion, including the following raw materials in percentage by mass: 63% aggregate, 10% calcined α-Al2O3 powder CL370, 10% fused spinel powder AMS-78, 10% plate-shaped corundum powder, 2.5% fused magnesium powder, 0.5% silicon powder, 4% binder, and 2% water; wherein, The aggregate includes the following raw materials in percentage by mass: 11% of coarse powder of reduced aluminum-chromium slag with a particle size of 3-5 mm; 32% of medium powder of reduced aluminum-chromium slag with a particle size of 1-3 mm; 20% of fine powder of reduced aluminum-chromium slag with a particle size of 0-1 mm; and the coarse powder, medium powder and fine powder of reduced aluminum-chromium slag are all recycled granular materials produced by high-temperature heat treatment of aluminum-chromium slag by carbon thermal reduction method; The particle size of calcined α-Al2O3 powder is ≤0.044mm, the particle size of fused spinel powder AMS-78, plate-shaped corundum powder, and silica powder are 300~350 mesh respectively, and the particle size of fused magnesium powder is 150~200 mesh; The binder is a magnesium-aluminum complex gel binder chemically combined with inorganic water, and the magnesium-aluminum complex gel binder is 300-350 mesh; S2, mixing materials, first add 2~2.2% water to 48~72% aggregate (8~12% reduced aluminum chromium slag coarse powder, 25~35% reduced aluminum chromium slag medium powder, 15~25% reduced aluminum chromium slag fine powder) and stir until wet, then add 3~5% magnesium aluminum complex gel binder and stir for 5~7 minutes to make the binder completely melt and adhere to the aggregate, then add 8~12% calcined α-Al2O3 micro powder CL370, 8~12% fused spinel powder AMS-78, 8~12% plate-like corundum powder, 2~4% fused magnesium powder, 0.5~1% silicon micro powder and stir thoroughly for 25~30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; The technical indicators of the brick blank require a volume density of 3.0~3.05g / cm 3 , apparent porosity ≤12%, compressive strength at room temperature MPa≥60, flexural strength at room temperature MPa≥4; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
[0017] Example 4 Index Analysis: The chemical substances of the main raw materials meet the requirements and can be fully used as raw materials for magnesia-alumina spinel bricks. The specific indicators are shown in Table 1. The porosity, bulk density and compressive strength at room temperature (200℃*24h), medium temperature (1000℃*3h) and high temperature (1500℃*3h) are tested according to national standards and all meet the requirements of national standards. The specific data are shown in Table 2. The SEM photos and EDS analysis results of the crucible after the static slag resistance test are as follows: Figure 1 And as shown in Table 3. Through Table 3, Figure 1 It can be seen that the reduced aluminum-chromium slag particles react with the blast furnace slag, and the slag layer is mainly composed of feldspar (such as Figure 1 Point 1, point 2) and a small amount of spinel (such as Figure 1 Point 3 in the figure); a dense layer of calcium feldspar (such as Figure 1Point 5 in the figure) is about 30 to 60 μm thick, and there is a loose spinel layer outside. The reduced aluminum-chromium slag does not directly contact and react with the blast furnace slag under the double-layer protection, so it has high stability and strong resistance to slag corrosion.
Claims
1. A magnesia-alumina spinel brick produced from aluminum-chromium slag, characterized in that: The invention comprises the following raw materials in percentage by weight: 48-72% aggregate, 8-12% calcined α-Al2O3 powder CL370, 8-12% fused spinel powder AMS-78, 8-12% plate-like corundum powder, 2-4% fused magnesium powder, 0.5-1% silicon powder, 3-5% binder and 2-2.2% water.
2. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim 1, characterized in that: The raw materials include the following mass percentages: 63% aggregate, 10% calcined α-Al2O3 powder CL370, 10% fused spinel powder AMS-78, 10% plate-like corundum powder, 2.5% fused magnesium powder, 0.5% silicon powder, 4% binder, and 2% water.
3. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim 1, characterized in that: The aggregate comprises the following raw materials in percentage by mass: 8-12% of coarse reduced aluminum-chromium slag powder, 25-35% of medium reduced aluminum-chromium slag powder, and 15-25% of fine reduced aluminum-chromium slag powder.
4. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim 3 is characterized in that: The particle size of the reduced aluminum-chromium slag coarse powder is 3-5 mm, the particle size of the reduced aluminum-chromium slag medium powder is 1-3 mm, and the particle size of the reduced aluminum-chromium slag fine powder is 0-1 mm.
5. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim 1, characterized in that: The particle size of the calcined α-Al2O3 powder is ≤0.044 mm, the particle size of the fused spinel powder AMS-78, the plate-shaped corundum powder and the silicon powder are 300-350 meshes respectively, and the particle size of the fused magnesium powder is 150-200 meshes.
6. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim 1, characterized in that: The reduced aluminum-chromium slag is a regenerated granular material produced by subjecting the aluminum-chromium slag to high-temperature heat treatment using a carbon thermal reduction method.
7. The magnesia-alumina spinel brick produced from aluminum-chromium slag according to claim, characterized in that: The binder is a magnesium-aluminum complex gel binder chemically combined with inorganic water, and the magnesium-aluminum complex gel binder has a mesh size of 300-350.
8. A method for preparing magnesia-alumina spinel bricks produced from aluminum-chromium slag according to any one of claims 1 to 7, characterized in that: The specific steps include: S1. Prepare the materials, mix various raw materials according to the proportion and set aside; S2, mixing materials, first add water to the aggregate (reduced aluminum chromium slag coarse powder, reduced aluminum chromium slag medium powder, reduced aluminum chromium slag fine powder) and stir until wet, then add magnesium aluminum complex gel binder and stir for 5-7 minutes to make the binder completely melt and adhere to the aggregate, then add calcined α-Al2O3 micro powder CL370, fused spinel powder AMS-78, plate-like corundum powder, fused magnesium powder, and silicon micro powder and stir thoroughly for 25-30 minutes to obtain mud. The mixed mud should be able to form a mass by lightly kneading, and finally the mud is trapped, and the trapping time shall not exceed 4 hours; S3, molding, put the mud into a 630t electric screw press to form, punch 3 times with light hammer and 4 times with heavy hammer to get the brick, the density of the brick after molding is controlled at 3.0~3.05g / cm 3 ; S4. Drying: Dry the formed bricks in a countercurrent tunnel dryer or an electric heating tunnel dryer at 180-220° C. for 12 hours to obtain finished magnesia-alumina spinel bricks.
9. The method for preparing magnesia-alumina spinel bricks produced from aluminum-chromium slag according to claim 8, characterized in that: The technical index of the bricks in step S3 is: volume density 3.0~3.05g / cm 3 , apparent porosity ≤12%, compressive strength at room temperature MPa≥60, flexural strength at room temperature MPa≥4.
Citation Information
Patent Citations
Al2O3-Cr2O3-MgO firebrick
CN103936434A
Alumina-spinel-carbon brick containing aluminachrome slag and preparation method of alumina-spinel-carbon brick
CN104496502A
Chromium corundum-magnesia-alumina spinel brick used for zinc volatilization kiln and preparation method thereof
CN107140957A
Regenerated aluminum-chromium brick for Ausmelt copper smelting furnace and preparation method thereof
CN107739195A
Cement-free aluminum-magnesium-chromium castable taking aluminum-chromium slag as main raw material as well as preparation method and application of cement-free aluminum-magnesium-chromium castable
CN112679201A